Gut microbiota and autoimmune neurologic disorders: a two-sample bidirectional Mendelian randomization study - Zhang, Mengyuan; Fang, Jie; Zheng, Chamou; Lin, Qing; Zhang, Jiawei (Frontiers in Microbiology, 2024)
Background: Increasing evidence has suggested that alterations in the gut microbiome are correlated with autoimmune neurologic disorders, yet the causal relationship between them has yet to be established.From the published genome-wide association study (GWAS) summary statistics, we obtained data on the gut microbiota and three autoimmune neurologic disorders (Multiple Sclerosis, Guillain-Barré Syndrome, and Myasthenia Gravis). We then implemented a two-sample Mendelian Randomization (MR) to determine the causal relationship between the gut microbiota and the diseases. To validate the results, we conducted a series of sensitivity analyses. Finally, to verify the direction of causality, a reverse-causality analysis was done.Results: We discovered that a higher relative abundance of the genus Ruminococcus2